Self-reported perceptions of adults with diabetes regarding their care and health in the time of COVID-19 pandemic in a Swiss region: a cross-sectional study - Christophe Kosinski; Emilie Zuercher; Tania Carron; Julie Chevallereau; Marie-Annick Le Pogam; Chiara Storari; Anne Wojtusciszyn; Isabelle Peytremann-Bridevaux (Swiss Medical Weekly)
AIM: To assess the perceptions of adults with diabetes regarding their care and health during the COVID-19 pandemic in the canton of Vaud, Switzerland.